Peningkatan Pemahaman Karyawan Dalam Penggunaan Excel Untuk Pengelolaan Inventory - Sanwani Sanwani; Eko Setia Budi; Eva Zuraidah; Ade Priyatna; Besus Maulana Sulthon (Journal of Social Responsibility Projects by Higher Education Forum, 2021)
The obligations to each university as described in the Tridharma of Higher Education are education, research, and community service. One form of this obligation at the Nusa Mandiri School of Information and Computer Management (STMIK) is to carry out community service. This is carried out in relation to the concern of every institution or institution engaged in education by following technological developments and advances. This time, community service was carried out at PT. Jaya Persada Indonesia or JPI is a company that was founded with a spirit of togetherness, seeing opportunities for the development of its property and human resources, so the company is currently focusing on the business area carried out by PT. Jaya Persada Indonesia is a Property Developer, Property Agency (JPI Propertindo). Limited understanding of the Microsoft Excel program for office inventory, therefore the Nusa Mandiri College of Information and Computer Management conducted Community Service in the form of Excel Training Workshop Training for Inventory kator at PT. Jaya Persada Indonesia (PT. JPI) in East Jakarta. With this training, it can help management in managing inventory activities at PT. Jaya Persada Indonesia (PT. JPI).